2012
DOI: 10.1021/ac3024312
|View full text |Cite
|
Sign up to set email alerts
|

Trace-Level Potentiometric Detection in the Presence of a High Electrolyte Background

Abstract: Polymeric membrane ion-selective electrodes (ISEs) have become attractive tools for trace-level environmental and biological measurements. However, applications of such ISEs are often limited to measurements with low levels of electrolyte background. This paper describes an asymmetric membrane rotating ISE configuration for trace-level potentiometric detection with a high-interfering background. The membrane electrode is conditioned in a solution of interfering ions (e.g., Na + ) so that no primary ions exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 32 publications
(57 reference statements)
1
50
0
Order By: Relevance
“…The results are summarized in Table 1. It can be seen that the potentiometric selectivity coefficients of the proposed solid-contact electrode are comparable to those of the conventional liquid-contact electrode based on the same ionophore [34].…”
Section: Preparation Proceduresmentioning
confidence: 75%
“…The results are summarized in Table 1. It can be seen that the potentiometric selectivity coefficients of the proposed solid-contact electrode are comparable to those of the conventional liquid-contact electrode based on the same ionophore [34].…”
Section: Preparation Proceduresmentioning
confidence: 75%
“…However, our previous studies indicate that there is no obvious sensitivity change of the asymmetric membrane electrode within 2 weeks. 29 Moreover, researchers have shown that the immunosensor based on the polymeric membrane exhibited satisfactory long-term stability and reliability. 30 2.6.…”
Section: Methodsmentioning
confidence: 99%
“…The potential responses were measured by a polycation-sensitive membrane electrode with a rotating electrode configuration (3000 rpm) as described before (see the Supporting Information). 11 Before measurements, the electrodes were conditioned in 0.01 M NaCl for 5 min to obtain a stable baseline.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…9 However, most of the successful applications of ISEs are still limited to detection of a number of ionic species, and low levels of electrolyte backgrounds are usually required for the low detection limit measurements. 10,11 It thus remains a challenge to apply potentiometric sensors to detect a broad range of different molecular targets with high sensitivity, especially in complex media (e.g., clinical or environmental samples).…”
mentioning
confidence: 99%